Diseño mecánico y sistema automatizado contra incendios de un tanque atmosférico de techo cónico de 25000 barriles, para almacenamiento de hidrocarburos. - Alvarado Rodríguez, Óscar Leonardo (2010)
The storage constitutes an element of extreme value in the operation of the services of hydrocarbons since it acts as a lung between production and transport to absorb the consumption variations. In Chapter I, REVISION OF LITERATURE. A summary is realized, of the identity and history of the Industrial Complex Shushufindi, its capacities of production and storage, its substations of refinement, distribution of its derivatives. The enterprise structuring, the listing of Storage caves available, Conical and Floating. The study Software Sima tic S7-200 for the programming of the system against fires. In chapter II, MATERIALS AND METHODS. It is realized, a description of the used materials of the design of the tank, according to the specification of Standard API 650, the type of meetings to use, as much for the bottom, body, ceiling, accessories of the tank, I am realized the programming of Software Sima tic S7-200 for the automatization of the system against fires. In Chapter III RESULTS. I am realized the calculations of the design of the atmospheric tank of conical ceiling, and the simulation of Software Sima tic S7-200 for its respective verification and operation. In Chapter IV DISCUSSION. In order to come with the validation of the results given by the thesis project, they were analyzed by means of two sources of intelligence. Using standard API the 650 and memories used by Shushufindi Refinery, I am realized an analysis between Software LOGO and SIMATIC last S7-200 being this most suitable one and used in the present project. Chapter V, CONCLUSIONS AND RECOMMENDATIONS. They are the result of an arduous work altogether of its authors, personal plenty of knowledge, experiences and exigencies, to satisfy the proposed objectives.